Penerapan Lubang Resapan Biopori Dalam Meningkatkan Laju Infiltrasi di Desa Sungai Langka - Nadia Dhannov; Irhamni; Fajriharish Nur Awan; Mutiara Fajar; Nabila Putriyandri Alifa; Yuni Lisafitri; Sillak Hasiany (Jurnal Serambi Engineering, 2025)
The Sungai Langka Village area lacks drainage and has elevated roads, causing water to run off during rainfall and onto the roads and into people's yards. In these conditions, efforts will be made to utilise water runoff as an alternative water source. This study aims to determine the effect of infiltration in the application of biopori infiltration pit technology. This research was conducted using a quantitative approach. The data were processed using the Horton method and analysed descriptively. Infiltration data was collected in situ in the field. The data compared the infiltration rate before and after the application of biopori infiltration pits. The results showed that the infiltration rate was constant at 46 cm/hour, 44 cm/hour, 32 cm/hour, 36 cm/hour and 32 cm/hour before the application of biopori infiltration pits. Meanwhile, the infiltration rates after the application of biopore infiltration pits were 110 cm/hour, 78 cm/hour, 70 cm/hour, 104 cm/hour and 138 cm/hour. The aim of the study was to determine how increasing infiltration rates can reduce water runoff and increase groundwater reserves.